An Assessment of the Effect of Terracing on the Physical Properties of Soils - Jagtap, S.M.; Zende, G.K. (Journal of Soil and Water Conservation, 2022)
Top soil is the farmers principal asset, and it is upon the productiveness of this layer that agricultural activities ultimately depend. The process of soil formation ispretty slow and it takes many years to build up one centimetre layer of soil. The process of soil formation and its denudation are taking place simultaneously. Basu and Puranik (I) have estimated that the loss of soil through erosion from unprotected fields is often as high as 50 tonnes per acre annually and may actually go up as high as 130 tonnes per acre in a single year. The great and vital importance of conserving this nit: tures gift is therefore obvious.